Pemberdayaan masyarakat melalui pelatihan pembuatan pakan probiotik untuk meningkatkan ketahanan pangan Ternak kambing - Subandi; Ermanita Permatasari; Baharudin; Ihsan Mustofa; Suci Amalia (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2025)
East Lampung has more than 80% of business units in the micro, small and medium industry sector, including livestock businesses. East Lampung produces 173,576 goats per year spread across twenty-four sub-districts. The monitored community activities aim to utilize an organized community. The community has assets to realize economic independence through a goat livestock program that makes probiotic feed from clean water, yakult, tempeh yeast, brown sugar and old coconut water. Monitoring uses the ABCD (asset-based community development) method, so that it can develop assets owned by the community so that they can be economically independent and improve community welfare. The results achieved are strengthening the capacity of goat farmers' skills in making probiotic feed and producing community economic welfare and sustainable food security.